Ultrafine Viscose‐Based Active Carbon Fibers for Iodide‐Ion Adsorption and Supercapacitors. Issue 18 (15th July 2022) - Wu, Qianqian; Cai, Yi; Li, Kunming; Zeng, Fanlong; Ju, Anqi
Abstract : Active carbon fibers (ACFs) with a large specific surface area (SSA) have received widespread attention in various fields, such as environmental treatment and energy storage. Herein, ultrafine viscose‐based active carbon fibers (UVACFs) with large SSAs and micropores are successfully prepared via stabilization, carbonization, and CO2 activation using ultrafine viscose fibers (UVFs) as precursors. The microporous structure and SSA of UVACFs are adjusted by the activation temperature and the morphology and structure are characterized by a scanning electron microscope, X‐ray diffraction, Raman spectroscopy, and N2 adsorption/desorption. As a result, the SSA of UVACFs can reach 591.58 m 2 g −1 with the main pore size of 0.52 nm under activation temperature of 900 °C. The adsorption capacity of UVACFs‐900 for iodide ions is as high as 830.3 mg g −1, which is the highest one among reported ACFs. It is attributed to the fact that the pore size of as‐prepared UVACFs is close to the hydration radius of iodide ions (0.335 nm). Moreover, NiCo2 O4 is grown uniformly on UVACFs by the hydrothermal method, which shows high capacitance of 2693.3 F g −1 at 1 A g −1 and excellent cycling stability with 94.5% capacity retention after 3000 cycles (10 A g −1 ). Abstract : Ultrafine viscose fbers are used as precursors to prepare the viscose‐based active carbon fibers with large specic surface area. The prepared UVACFs‐900 has great adsorption on iodide ion and uaed as supercapacitor.